Guidelines for the correct use of the nomenclature of biochemical indices of bone status: a position statement of the Joint IOF Working Group and IFCC Committee on Bone Metabolism - Lombardi, Giovanni; Jørgensen, Niklas Rye; Harvey, Nicholas C; McCloskey, Eugene V; Åkesson, Kristina E; Eastell, Richard; Garnero, Patrick; Kanis, John A; Khashayar, Patricia; Lane, Nancy E; McClung, Michael R; Silverman, Stuart; et al. (Clinical chemistry and laboratory medicine, 2025)
The presented guidelines are an update of the position paper, endorsed by the International Osteoporosis Foundation (IOF), on nomenclature of bone markers published over 2 decades ago. Novel insight into bone biology and pathophysiology of bone disorders has highlighted the increasing relevance of new and known mediators implicated in various aspects of bone metabolism. This updated guideline proposes the nomenclature Bone Status Indices (BSI) as the comprehensive classification rather than bone turnover markers, bone markers, metabolic markers of bone turnover or metabolic markers of bone turnover, that are currently in use for the implicated molecules. On behalf of the IFCC Committee on Bone Metabolism and the Joint IOF Working Group and IFCC Committee on Bone Metabolism, the authors propose standardized nomenclature, abbreviations and measurement units for the bone status indices.
Keywords: terminologie jako téma; Terminology as Topic; Bone and Bones; Osteoporosis; nomenclature; Humans; biologické markery; kosti a kostní tkáň; lidé; Biomarkers; bone status indices; standardization; osteoporóza